The berth scheduling problem with customer differentiation: A new methodological approach based on hierarchical optimization - Saharidis, G. K.D.; Golias, Mihalis; Boile, M.; Theofanis, S.; Ierapetritou, M. G. (My University, 2010)
The berth scheduling problem deals with the assignment of vessels to berth space in a container terminal. Defining berth schedules in container terminal operations translates in meeting different objectives that are often non-commensurable and gaining an improvement on one objective often causes degrading performance on the others. In this paper the discrete space and dynamic arrival berth scheduling problem is studied and formulated for the first time via a hierarchical optimization framework, using two levels of hierarchy that differentiate between two conflicting objectives terminal operators face when defining vessel to berth assignments. For the resolution of this problem an interactive algorithm is developed based on the k-th best algorithm for the case where multi-objective functions are considered in the upper level. Computational examples showed that the proposed algorithm gives optimal or near optimal solutions that are comparable to the ones obtained by its single level formulation counterpart. © 2009 Springer-Verlag London Limited.